Oxygen uptake kinetics in peripheral arterial disease - Bauer, Timothy Alan (Kansas State University, 2005)
Peripheral arterial disease (PAD) is a manifestation of the systemic disease of atherosclerosis that results in arterial stenoses of the lower extremities. Patients with PAD demonstrate slowed dynamics of pulmonary oxygen uptake (VO2 kinetics) following the onset of exercise and a profound reduction in peak oxygen uptake and work capacity. However, whereas the primary pathophysiology of PAD results from the lower extremity hemodynamic limitation, there are abnormalities distal to the arterial stenoses in PAD-affected skeletal muscle that may also contribute to the impaired exercise responses. Thus, the potential contributions of abnormal muscle metabolism versus local circulatory defects in the PAD exercise impairment remains unclear. In this context, the purpose of the dissertation was to advance our understanding of the abnormal pulmonary VO2 kinetics in PAD and characterize the local muscle deoxygenation responses during the rest-exercise transition exercise in health and PAD. The present series of investigations were designed to: 1. localize the abnormal pulmonary VO2 kinetics in PAD to the affected lower extremities, 2. characterize the kinetics of calf muscle deoxygenation during walking in PAD and healthy subjects, 3. describe muscle deoxygenation kinetics in relation to exercise work rate and blood flow in PAD and health, and 4. evaluate the effect of arterial revascularization on pulmonary VO2 kinetics in PAD. These investigations revealed a persistent abnormality in muscle oxygen utilization in PAD-affected skeletal muscle that was not associated with the severity of hemodynamic compromise. In particular, we observed slowed pulmonary VO2 kinetics in PAD only during exercise of the PAD-affected skeletal muscles. Moreover, muscle deoxygenation kinetics following the onset of walking and lower intensity calf exercise were prolonged in PAD subjects while leg blood flow responses were normal. However, at higher work rates, PAD muscle deoxygenation kinetics accelerated, demonstrating a work rate and presumably blood flow dependence. Lastly, arterial revascularization tended to improve, but not consistently normalize, pulmonary VO2 kinetics in PAD subjects. Thus, these investigations demonstrate abnormal oxygen uptake kinetics in PAD and provide evidence that local abnormalities of the affected skeletal muscle may contribute to the abnormal VO2 kinetics and exercise intolerance of patients with PAD.
Keywords: Exercise; Oxygen uptake; Arterial disease; Muscle; Biology, Anatomy (0287); Health Sciences, Rehabilitation and Therapy (0382)Health Sciences, Recreation (0575)